Statistical Properties of Ideal Ensemble of Disordered 1D Steric Spin-Chains - Gevorkyan, Ashot S.; Abajyan, Hakob G.; Sukiasyan, Hayk S. (Mathematical Problems of Computer Science, 2021)
The statistical properties of ensemble of disordered 1D steric spin-chains (SSC) of various length are investigated. Using 1D spin-glass type classical Hamiltonian, the recurrent trigonometrical equations for stationary points and corresponding conditions for the construction of stable 1D SSCs are found. The ideal ensemble of spin-chains is analyzed and the latent interconnections between random angles and interaction constants for each set of three nearest-neighboring spins are found. It is analytically proved and by numerical calculation is shown that the interaction constant satisfies Lévy's alpha-stable distribution law. Energy distribution in ensemble is calculated depending on different conditions of possible polarization of spin-chains. It is specifically shown that the dimensional effects in the form of set of local maximums in the energy distribution arise when the number of spin-chains M << N2 x (where Nx is the number of spins in a chain) while in the case when M / N2 x energy distribution has one global maximum and the ensemble of spin-chains satisfies Birkhoff's ergodic theorem. Effective algorithm for parallel simulation of problem which includes calculation of different statistic parameters of 1D SSCs ensemble is elaborated.